A Central Symmetrical and Low-Profile Omnidirectional Circularly Polarized Antenna - Zhe Wu; Lin Yang; Jiaji Wu; Zhensen Wu; Xi Li; Yu Yun (International Journal of Antennas and Propagation)
In this paper, a compact circularly polarized (CP) antenna with omnidirectional radiation is presented, which has a central symmetric configuration (CSC) and planar structure. It consists of three identical end-fire CP antenna units. Based on the combination of two parallel complementary current sources, each unit cell can be realized by a scalloped cavity and a couple of curved strip lines. Due to a single-layer circular structure with low profile, this configuration can be excited by a coaxial probe in the centre of the whole frame simultaneously. In addition, this prototype was miniaturized with a diameter of 32 mm (0.266λr, the wavelength of the centre frequency in free space is represented by λr) and a height of 1.5 mm (0.012λr). Centre resonance frequency 2.492 GHz is selected, resulting in an omnidirectional radiation and impedance bandwidth (VSWR ≤ 2) of 25 MHz (2481–2506 MHz).